The point of a Guillemot's egg. (23rd February 2017) - Birkhead, Tim R.; Thompson, Jamie E.; Jackson, Duncan; Biggins, John D.
Abstract : The adaptive significance of avian egg shape in birds is poorly understood. The pyriform (pear‐like) shape of the Common Guillemot's Uria aalge egg has long been considered to be an adaptation to prevent eggs rolling off the bare cliff ledges on which this species breeds. Rolling was thought to be prevented either by the egg spinning like a top, which is not the case, or by rolling in an arc, which it does but with little influence on whether the egg will fall from a ledge. We therefore sought alternative explanations for the pyriform shape of the Common Guillemot's egg. This species breeds in extremely dense colonies, which makes their eggs vulnerable to mechanical damage from conspecifics, and to contamination by debris such as faeces and soil. We present evidence consistent with both these possible explanations. First, the pyriform shape of Common Guillemot eggs means that a higher proportion of the eggshell lies in contact with the substrate and this may minimize the effect of impacts. Resistance to impacts may be further enhanced because their eggshells are especially thick where they are in contact with the substrate. Secondly, Common Guillemot eggs are often heavily contaminated with faecal material and other debris during incubation. Most contamination is on the pointed end of the egg where it is in contact with the substrate; the pyriform shape thus keeps the blunt end of the egg, which has the highest porosity, relatively free of contamination, which in turn may facilitate both gas exchange during incubation and the hatching process, because the chick emerges from the blunt end of the egg.